2014
DOI: 10.1002/ijc.28850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of gastric cancer with miRNA clusters including the cancer‐related genes MIR29, MIR25, MIR93 and MIR106: Results from the EPIC‐EURGAST study

Abstract: MicroRNAs (miRNAs) are post-transcriptional gene regulators involved in a wide range of biological processes including tumorigenesis. Deregulation of miRNA pathways has been associated with cancer but the contribution of their genetic variability to this disorder is poorly known. We analyzed the genetic association of gastric cancer (GC) and its anatomical and histological subtypes, with 133 single-nucleotide polymorphisms (SNPs) tagging 15 isolated miRNAs and 24 miRNA clusters potentially involved in cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…The miR‐29 expression was significantly decreased in skin biopsy samples or the biopsy sample derived fibroblasts cultured in vitro of patients with scleroderma (Tatmatsu‐Rocha et al, ). At the same time, knockdown or downregulation expression of miR‐29 in lung fibroblasts could activate fibrosis‐related genes in vitro (Espinosa‐Parrilla et al, ; Qu, Zhu, Tao, & Zhao, ). More evidence showed that downregulation of miR‐29 in cardiac fibroblasts could induce the expression of fibrosis related genes both in vivo and in vitro, while high expression could inhibit fibrosis (Gao, Qiao, Lu, & Hou, ; Qu et al, ).…”
Section: The Epigenetic Mechanism Regulating the Formation Of Myofibrmentioning
confidence: 99%
“…The miR‐29 expression was significantly decreased in skin biopsy samples or the biopsy sample derived fibroblasts cultured in vitro of patients with scleroderma (Tatmatsu‐Rocha et al, ). At the same time, knockdown or downregulation expression of miR‐29 in lung fibroblasts could activate fibrosis‐related genes in vitro (Espinosa‐Parrilla et al, ; Qu, Zhu, Tao, & Zhao, ). More evidence showed that downregulation of miR‐29 in cardiac fibroblasts could induce the expression of fibrosis related genes both in vivo and in vitro, while high expression could inhibit fibrosis (Gao, Qiao, Lu, & Hou, ; Qu et al, ).…”
Section: The Epigenetic Mechanism Regulating the Formation Of Myofibrmentioning
confidence: 99%
“…It is also revealed that miR‐126 facilitates angiogenesis of GC through regulating vascular endothelial growth factor (VEGF) level, which is an important regulator in vasculogenesis 18. These studies indicate that miRNAs are involved in angiogenesis, and aberrant expressions of these miRNAs are associated with etiology and progression in cancers 24, 25, 26, 27, 28. However, the predictive value of angiogenesis‐related miRNAs in GC is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Overlapping genes found commonly in CNGs of 7q31.2–q32 regions were KCND2 , MIR29A , MIR29B1 , FJ43663 , and MKLN1. MIR29A and MIR29B1 are known as tumor suppressor miRNAs that inhibit the progression of several cancer types and may potentially serve as candidate positive prognostic factors . The intrinsic genes in 8q11.1 are less characterized but may also include unknown prognostic factors (genes) for mCRC .…”
Section: Discussionmentioning
confidence: 99%